A three-component reagent system for rapid and mild removal of O-, N- and S-trityl protecting groups. Issue 12 (9th February 2016) - Kicsák, Máté; Bege, Miklós; Bereczki, Ilona; Csávás, Magdolna; Herczeg, Mihály; Kupihár, Zoltán; Kovács, Lajos; Borbás, Anikó; Herczegh, Pál
Abstract : A synergistic effect of BF3 ·Et2 O, hexafluoroisopropanol and triethylsilane led to efficient detritylation of nucleoside, monosaccharide and amino acid derivatives. Abstract : A new reagent system consisting of a Lewis acid such as BF3 ·Et2 O or Cu(OTf)2, the mild protic acid hexafluoroisopropanol and the reducing quenching agent triethylsilane was elaborated for O -, N - and S -detritylation of nucleoside, carbohydrate and amino acid derivatives. The method is compatible with acetyl, silyl, acetal and Fmoc groups.